Cataract : Wij zijn in de wereld gevogeld maar kunnen niet vliegen. - Boermans, Theu; van der Laan, Anke (Heerlen : Stadsgalerij, 1998)
Billingham, Richard ; Brothers Chapman ; Brus, Günter ; ten Cate, Ritsaert ; Dijkstra, Rineke ; Dubuffet, Jean ; de Haas, Aad ; Kamphuis, Ivo ; Kiefer, Anselm ; Mulders, Marc ; Nitsch, Hermann ; Ophuis, Ronald ; Rainer, Arnulf ; Stelarc ; van Warmerdam, Marijke
Cataract : Wij zijn in de wereld gevogeld maar kunnen niet vliegen, Stadsgalerij, Heerlen, 21 juni t/m 13 september 1998
Nederlands
boek